2022
DOI: 10.1111/gcb.16067
|View full text |Cite
|
Sign up to set email alerts
|

Optimum growth temperature declines with body size within fish species

Abstract: Individual body growth is a fundamental process powered by metabolism, and thus depends on body size and temperature (Brown et al., 2004). It affects individual fitness and life-history traits, such as maturation size, population growth rates (Savage et al., 2004), and ultimately energy transfer across trophic levels (Andersen et al., 2009;Barneche & Allen, 2018). Therefore, understanding how growth

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 145 publications
0
47
1
Order By: Relevance
“…In this regard, our findings show that the larger conspecifics living at lower latitudes, owing to either the limitation of the performance of metabolic enzymes or the availability of oxygen, could be the first to experience the negative impacts of future warming on performance and other metabolism-related processes. This adds to growing evidence that physiological constraints at warmer temperatures reduce the performance of large-bodied individuals to a greater degree than their small-bodied conspecifics ( Lindmark et al, 2022 ). This in turn affects population size structure in the face of climate change, particularly in populations living at the edge of their physiological tolerance ( Huss et al, 2019 ; Neuheimer et al, 2011 ).…”
Section: Discussionmentioning
confidence: 81%
“…In this regard, our findings show that the larger conspecifics living at lower latitudes, owing to either the limitation of the performance of metabolic enzymes or the availability of oxygen, could be the first to experience the negative impacts of future warming on performance and other metabolism-related processes. This adds to growing evidence that physiological constraints at warmer temperatures reduce the performance of large-bodied individuals to a greater degree than their small-bodied conspecifics ( Lindmark et al, 2022 ). This in turn affects population size structure in the face of climate change, particularly in populations living at the edge of their physiological tolerance ( Huss et al, 2019 ; Neuheimer et al, 2011 ).…”
Section: Discussionmentioning
confidence: 81%
“…Experimentally determined optimum growth temperatures for sockeye salmon are around 15°C when excess food is available, but decline when food becomes limiting, to as little as 5°C for feeding rates of 1.5% of dry body weight per day [ 51 ]. While the experiments were conducted using juveniles, warm conditions that reduce growth may be reached at even lower temperatures in adult sockeye salmon, because optimal growth temperatures commonly decline with body size in fishes [ 52 ]. It is well known that the effects of increasing temperatures can differ between low- and high-competition environments, because warming-induced growth changes depend on food availability [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…We approached this by applying random parameterization, rather than fixed values of temperature dependence. To capture the uncertainty of our approach, we sampled parameters from distributions based on estimates of activation energies of physiological rates in the literature (Lindmark et al, 2022 ). This approach revealed that in terms of body growth and mean body size in populations, the combination of activation energies can determine whether the mean size increases or decreases with warming, and at what age body sizes decline relative to the current temperatures (degree of decline in size‐at‐age).…”
Section: Discussionmentioning
confidence: 99%
“…Righton et al, 2010 as an example for cod), whereafter physiological rates might be expected to decline. While temperature likely affects other physiological processes as well (such as cost of growth [Barneche et al, 2019 ] or food conversion efficiency [Handeland et al, 2008 ]), we focus on the temperature effects on metabolism, maximum consumption, search volume and mortality, as their temperature dependencies are relatively well documented (Brown et al, 2004 ; Dell et al, 2011 ; Englund et al, 2011 ; Lindmark et al, 2022 ; Pauly, 1980 ; Thorson et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation